Something's Gotta Give Charleston Conference Proceedings, 2011 - Strauch, Katina P.; Hinds, Leah H.; Bernhardt, Beth R. (Purdue University Press, 2012)
The theme of the 2011 Charleston Conference, the annual event that explores issues in book and serial acquisition, was "Something's Gotta Give." The conference, held November 2-5, 2011, in Charleston, SC, included 9 pre-meetings, more than 10 plenaries, and over 120 concurrent sessions. The theme reflected the increasing sense of strain felt by both libraries and publishers as troubling economic trends and rapid technological change challenge the information supply chain. What part of the system will buckle under this pressure? Who will be the winners and who will be the losers in this stressful environment? The Charleston Conference continues to be a major event for information exchange among librarians, vendors, and publishers. As it begins its fourth decade, the Conference is one of the most popular international meetings for information professionals, with almost 1,500 delegates. Conference attendees continue to remark on the informative and thought-provoking sessions. The Conference provides a collegial atmosphere where librarians, vendors, and publishers talk freely and directly about issues facing libraries and information providers. In this volume, the organizers of the meeting are pleased to share some of the learning experiences that they-and other attendees-had at the conference.